Positive Bank Resource Management Experience in Foreign Countries - Ortikov Uygun Davlatovich; Khamrokhujaeva Sitorabonu Temur kizi (European Journal of Life Safety and Stability (2660-9630), 2023)
The idea of banking resources is defined in this article, which also looks at the theoretical underpinnings of how commercial banks and the Central Bank handle them. The study is conducted in a number of resource management areas, including examination of own and borrowed money, capital sufficiency, profitability, etc. Additionally, it outlines the procedures for planning the administration of the bank’s financial resources across several nations. Therefore, strategies for converting money and general-purpose funds that have become common in Russian Federation practice are taken into account. It is being researched how Chinese banks have handled the application of the financial resource management plan. As well as managing distressed assets in some European and developing countries.